Inflation in Central Europe from the Late Middle Ages to the early 19th Century - Vorel, Petr (My University, 2023)
The author focuses on the three most important inflationary waves that hit Central Europe from the mid-15th century to the early 19th century. Using the example of the Kingdom of Bohemia, he shows how the causes and course of the inflationary currency collapse differed. They were all related to wartime events, but each time to a different extent and in a different context. In the first case, it is the imported inflation of 1458-1460. This was caused in Bohemia by the unregulated importation of foreign (Austrian and South German) small credit coins, which were granted high payment power in the domestic currency. However, the inflationary collapse of the currency concerned only small coins. In the second case, the inflation of 1621-1623 culminated in the devaluation of inflationary metal coins. This was not an immediate economic consequence of the war, but a deliberate devaluation of the currency through which the victorious Habsburg party. In the third case, from 1811-1816, the cause of the financial collapse of the Habsburg monarchy was the economic dislocation resulting from the long wars. In this case, the currency was devalued by the excessive printing of paper credit notes.
Inflace ve střední Evropě od pozdního středověku do počátku 19. století
Keywords: Inflation; currency; Central Europe; Kingdom of Bohemia; 1458-1460; 1621-1623; 1811-1816; Inflace; měna; střední Evropa; Království české; 1458-1460; 1621-1623; 1811-1816